2018
DOI: 10.1155/2018/6292410
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Choosing between Route Deviation and Point Deviation Policies for Flexible Transit Services

Abstract: Flexible transit services, which bring together the characteristics of fixed-route transit and demand-responsive transit, have been proven to be cost-efficient in low-density residential areas. In this paper, a methodology is proposed to assist planners in making better decisions when choosing between route deviation policy and point deviation policy, which are two promising types of flexible transit services. A user cost function is developed to measure the service quality of the transit systems, and analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Analyses of DRT performance should be based on both DRT system use and locational context, with specialized DRT applications especially dependent on context (Zheng, Li, & Qiu, 2018). In this paper an integrated transport and land-use approach was selected to explore methods for DRT service comparison (Te Brömmelstroet & Bertolini, 2009).…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Analyses of DRT performance should be based on both DRT system use and locational context, with specialized DRT applications especially dependent on context (Zheng, Li, & Qiu, 2018). In this paper an integrated transport and land-use approach was selected to explore methods for DRT service comparison (Te Brömmelstroet & Bertolini, 2009).…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Most of the studies on public transit user preferences focus on the competition between fixed route and demand responsive services (8,9). Few studies have focused on flexible route transit more generally (10). In Broome et al (11), the authors completed a study showing the public's positive perception of flexible transit systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the many types of flexible transit service, deviated fixed route services are the most widely used (14). In Zheng et al (10), a methodology is proposed to support the decision-making process when choosing between a route deviation policy and a point deviation policy. In Nourbakhsh and Ouyang (15), the agency and user cost components of a flexible transit system are analyzed considering idealized square cities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the spread of smartphones and electronic payments to all aspects of life, operating systems for instant information exchange and more flexible fare structures have become available via mobile phone apps and electronic payments. Subsequently, several studies of flexible public transit structures and strategies have been conducted under this new background [24][25][26]. The transit ridership is usually sensitive to fares, travel times, wait times, and access times, among other factors [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transit ridership is usually sensitive to fares, travel times, wait times, and access times, among other factors [27]. Some studies have revealed that flexible transit services are promising operating policies for shaping new travel patterns in low-demand areas [27][28][29][30] and that passengers are generally willing to use these innovative transit systems [4,24]. Many of these systems are well-structured flexible transit systems, but these systems do not precisely combine the actual characteristics of a flexible transit system with the heterogeneity characteristic of passengers' WTP; if we combine these two aspects, the bus company could earn more money, and passengers could get better personally designed service.…”
Section: Literature Reviewmentioning
confidence: 99%